Kajian Faktor Kinerja Sumber Daya Manusia Kontraktor Terhadap Kualitas Mutu Pekerjaan Proyek Kontruksi Jalan di Kota Sungai Penuh - Roli Darsa; Rini Nulyani; Zaitul Zaitul (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Infrastructure development in the regions is the key to creating an advanced and prosperous society, with a focus on road infrastructure as the engine of economic growth. In Sungaipuh City, the implementation of human resources in road construction projects from 2018-2022 has not been optimal. Of the 60 projects reviewed, around 50 projects demonstrated inadequate quality of human resource performance. The aim of the research is to explore human resource performance factors that influence project quality and strategies to improve them. The results show 37 variables that affect performance, including motivation, experience, compensation, human resource management, loyalty, discipline, work environment, competency, and capacity building and corporate image. This last factor has the greatest influence. To improve performance, the strategy includes comprehensive training, identification of training needs, selection of participants, application of technology in training, collaboration between stakeholders, overcoming employee turnover, and efficient budget management.